2021
DOI: 10.7759/cureus.15436
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of White Blood Cells and Nitrite in Dipstick Urinalysis in Association With Urine Culture in Detecting Infection in Adults From October 2016 to October 2019 at King Abdulaziz Medical City

Abstract: BackgroundUrinary tract infection (UTI) is one of the most common clinical presentations that exhaust the patients and confuse physicians. Some of the risk factors that contribute to UTIs are age, female gender, and diabetes. Urinalysis is used to detect abnormalities in the urine, such as the presence of leukocytes, blood, and nitrite. However, urinalysis accuracy depends on the patient and the analyzer. On the other hand, urine culture is considered gold standard for diagnosing UTI. For that, the aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…[ 16 ] and 62.7 % by Mohanna et al . [ 17 ] were all higher than the nitrite test, which is similar to the present study [ 15–17 ]. Most infections elicit an immune response and production of WBCs, which could explain why leucocyte esterase was a better UTI predictor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 16 ] and 62.7 % by Mohanna et al . [ 17 ] were all higher than the nitrite test, which is similar to the present study [ 15–17 ]. Most infections elicit an immune response and production of WBCs, which could explain why leucocyte esterase was a better UTI predictor.…”
Section: Discussionsupporting
confidence: 91%
“…Often, the L.E test has a better sensitivity than the nitrite test. The L.E sensitivity of 57.6 % reported by Prah et al [15], 92 % by Suresh et al [16] and 62.7 % by Mohanna et al [17] were all higher than the nitrite test, which is similar to the present study [15][16][17]. Most infections elicit an immune response and production of WBCs, which could explain why leucocyte esterase was a better UTI predictor.…”
Section: Discussionsupporting
confidence: 87%
“…As culture analysis can take several days to yield findings, there may be other viable methods for identifying urinary tract infections in ED settings [ 12 ]. Consequently, rapid and accurate diagnostic techniques with high sensitivity and specificity, such as urine dipsticks or urinalysis, can be beneficial in ED settings for detecting patients with suspected UTIs [ 13 , 14 ]. These tests can provide rapid answers and aid doctors in making prompt decisions on patient care and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found a low percentage of positivity in urine cultures. This could be explained by an inadequate handling of the samples, an initiation of antibiotic therapy prior to taking the samples due to self-medication by the patients, or a deficient selection of the samples that require a microbiological study, since it has been demonstrated that a positive result for leukocytes in the test strip as a predictor of bacterial growth has a lower performance than the bacterial count [ 53 , 54 ]. In addition, urine cultures were positive based on the commonly used threshold of >100,000 CFU/ml.…”
Section: Discussionmentioning
confidence: 99%